Unveiling Salt Tolerance Mechanisms and Hub Genes in Alfalfa (Medicago sativa L.) Through Transcriptomic and WGCNA Analysis - Fengdan Wang; Hanfu Wu; Mei Yang; Wen Xu; Wenjie Zhao; Rui Qiu; Ning Kang; Guowen Cui (Plants)
Alfalfa (Medicago sativa L.), an important forage crop with high nutritional value and good palatability, plays a vital role in the development of animal husbandry in China. In Northeast China, there are vast areas of saline–alkali land that remain undeveloped. Given that alfalfa is a highly adaptable forage crop, exploring its salt tolerance at the molecular transcriptional level and identifying salt-tolerant genes has great significance for breeding salt-resistant alfalfa varieties. This also provides valuable genetic resources for better utilization of saline–alkali land. In this study, we conducted two rounds of screening on 41 alfalfa varieties and identified WL168 as a salt-sensitive variety and Longmu801 as a salt-tolerant variety. After 7 days of 300 mM salt stress, both varieties showed a decreasing trend in plant height, fresh weight, and dry weight over time, but Longmu801 demonstrated better water retention ability compared to WL168. Chlorophyll content also declined, but chlorophyll a and total chlorophyll levels in Longmu801 were higher than in WL168. Hydrogen peroxide and malondialdehyde levels increased overall, but Longmu801 had significantly lower levels than WL168 under prolonged stress. Both varieties showed increasing trends in soluble sugars, proline, and antioxidant enzymes (SOD, POD, CAT), with Longmu801 significantly outperforming WL168. This suggests that the two varieties share similar growth and physiological response mechanisms, with their differences primarily arising from variations in indicator levels. In the above, comparisons between varieties were conducted based on the relative values of the indicators in relation to their controls. Transcriptomic analysis revealed that under salt stress, Longmu801 had 16,485 differentially expressed genes (DEGs) relative to its control, while WL168 had 18,726 DEGs compared to its control. Among these, 2164 DEGs shared the same expression trend, with GO functions enriched in response to oxidative stress, nucleus, plasma membrane, and others. The KEGG pathways were enriched in phenylpropanoid biosynthesis, protein processing in the endoplasmic reticulum, starch and sucrose metabolism, and others. This suggests that alfalfa’s transcriptional response mechanism to salt stress involves these pathways. Additionally, the variety-specific DEGs were also enriched in the same KEGG pathways and GO functions, indicating that the differences between the two varieties stem from their unique stress-responsive DEGs, while their overall mechanisms for coping with stress remain similar. To further identify salt stress-related genes, this study conducted WGCNA analysis using 32,683 genes and physiological indicators. Six modules closely related to physiological traits were identified, and the top five genes ranked by degree in each module were selected as hub genes. Further analysis of these hub genes identified five genes directly related to salt stress: Msa085011, Msa0605650, Msa0397400, Msa1258740, and Msa0958830. Mantel test analysis revealed that these genes showed strong correlations with physiological indicators. This study will provide important insights for breeding salt-tolerant alfalfa varieties.